2018
DOI: 10.3847/1538-4357/aaac29
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of Core-collapse Supernovae in Spatial Axisymmetry with Full Boltzmann Neutrino Transport

Abstract: We present the first results of our spatially axisymmetric core-collapse supernova simulations with full Boltzmann neutrino transport, which amount to a time-dependent 5-dimensional (2 in space and 3 in momentum space) problem in fact. Special relativistic effects are fully taken into account with a two-energy-grid technique. We performed two simulations for a progenitor of 11.2M ⊙ , employing different nuclear equations-of-state (EOS's): Lattimer and Swesty's EOS with the incompressibility of K = 220MeV (LS E… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
150
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 126 publications
(153 citation statements)
references
References 57 publications
3
150
0
Order By: Relevance
“…The disparity in the number densities between ν e andν e is reduced by the anti-correlation of their number fluxes in the same hemisphere, and a preferable condition for the ELN crossing is produced. It should be also noted that asymmetric neutrino emissions were not observed in our previous CCSN model (Nagakura et al 2018), which would be the main reason why Delfan Azari et al (2019) found no ELN crossings in the post-shock region.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…The disparity in the number densities between ν e andν e is reduced by the anti-correlation of their number fluxes in the same hemisphere, and a preferable condition for the ELN crossing is produced. It should be also noted that asymmetric neutrino emissions were not observed in our previous CCSN model (Nagakura et al 2018), which would be the main reason why Delfan Azari et al (2019) found no ELN crossings in the post-shock region.…”
Section: Discussionmentioning
confidence: 80%
“…The details of the code development of our Boltzmann solver are described in a series of papers Nagakura et al 2014Nagakura et al , 2017Nagakura et al , 2019d and its reliability has been well established by a detailed comparison to another Monte-Carlo neutrino transport code (Richers et al 2017). Some results of axisymmetric CCSN simulations by using our code can be seen in Nagakura et al (2018); Harada et al (2019); Nagakura et al (2019c).…”
Section: Ccsn Modelmentioning
confidence: 97%
See 1 more Smart Citation
“…Non-linear turbulent flows associated with convective overturn and the standingaccretion-shock-instability (SASI, Blondin et al (2003)) increase the neutrino heating efficiency in the gain region, essentially aiding the explosion (see Janka (2017a); Müller (2016); Hix et al (2016); Foglizzo et al (2015); Burrows (2013); Kotake et al (2012) for reviews). In fact, a growing number of neutrino-driven models have been reported so far in self-consistent two-dimensional (2D) simulations, which has supported the validity of the multi-D neutrino-driven mechanism (e.g., Marek & Janka (2009) ;Suwa et al (2010); Müller et al (2012a); Dolence et al (2014); Nakamura et al (2015); Pan et al (2016); O'Connor & Couch (2015); Burrows et al (2016); Summa et al (2016); Nagakura et al (2017); Müller et al (2017)). …”
Section: Introductionmentioning
confidence: 99%
“…However, consideration of higher moments (Pons et al 1998), full set of velocity dependent terms (equivalently treatment of full energy-group couplings in the transport equations), and neutrino-flavor coupling is surely needed for more sophisticated simulations (e.g., Rampp & Janka (2002a) In our multi-D simulations, we apply a ray-by-ray approach where the neutrino transport is solved along a given radial direction assuming that the hydrodynamic medium for the direction is spherically symmetric. This also remains to be updated with more advanced schemes (e.g., Skinner et al (2016); Nagakura et al (2017)). …”
Section: Three-flavor Idsa Schemementioning
confidence: 99%